The Progress of Cathode and Electrolyte for Low Temperature Sodium-Ion Battery - Zhou, Jingtong (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The expanding demand for efficient energy storage systems that operate effectively in low-temperature environments has led to increased research interest in sodium-ion batteries (SIBs) due to their affordability, safety, and the abundance of sodium resources. With the development of industry, SIBs need to face the challenge of extreme temperatures, especially at low temperatures where the decrease in ion conductivity leads to a significant decrease in SIB capacity. This review article presents a comprehensive analysis of the recent advancements, persisting challenges, and future perspectives of low-temperature SIBs. We begin by highlighting the fundamental challenges that impede the performance of SIBs at low temperatures, such as decreased ionic conductivity, increased charge transfer resistance, and the risk of sodium plating. The review then delves into innovative strategies that have been developed to enhance the low-temperature performance of SIBs. These strategies include the design of novel cathode materials with improved electronic and ionic conductivity, the synthesis of advanced electrolytes with lower freezing points and higher ionic conductivities, and the optimization of battery architecture to minimize adverse effects caused by low temperatures. This review aims to provide a solid foundation for researchers in the field of energy storage and to inspire further advancements in the development of high-performance low-temperature SIBs.